THE RELATIONSHIP BETWEEN FAMILY HISTORY, CONSUMPTION OF FRUITS AND VEGETABLES, AND PHYSICAL ACTIVITY AND HYPERTENSION - Farida Syamsi (Universitas Airlangga, 2019)
Background: The prevalence of hypertension in 2018 in Indonesia in people aged ≥ 18 years was 34.11%, an increasing trend compared to 2013, when it was 25.80%. Malang Region increased the prevalence of hypertension from 7.32% in 2016 to 9% in 2017. Purpose: This study aims to analyse the relationship between hypertension and the variables of family history, consumption of fruit and vegetables, and physical activity in Integrated Guidance Post Wajak District, Malang Region. Methods: This study is an observational study with a cross-sectional design. It used 2018 secondary data from P2PTM section of Provincial Health Agency of East Java. The total sample was 250 respondents in Integrated Guidance Post, Wajak District, Malang Regency. The independent variables were family history, consumption of fruit and vegetables, and physical activity, while the dependent variable was hypertension. Data were analysed using a chi-square test. Results: A significant relationship was found between the independent variables family history (p = 0.01; PR = 2.01; 95% CI = 1.21 < PR <3.34), consumption of fruit and vegetables (p = 0.02; PR = 1.89; 95% CI = 1.13 < PR <3.14), and physical activity (p = 0.00; PR = 2.85; 95% CI = 1.70 < PR < 4.77) and the dependent variable of hypertension. Conclusion: There was a relationship between the independent variables of family history, lack of consumption of fruit and vegetables, and lack of physical activity and the dependent variable of hypertension.